Reliability Analysis of a Controlled Stage-Constructed and Reinforced Embankment on Soft Ground Using 2D and 3D Models - Belo, Jean Lucas dos Passos; Lins da Silva, Jefferson (Frontiers in Built Environment, 2020)
Geosynthetic reinforcement has become a very practical technique to improve geotechnical structure safety. In spite of improved soil behavior, structures are affected by uncertainties related to soil and reinforcement material properties. This paper aims to present a reliability analysis in order to take statistical information (uncertainties) into account in a safety analysis of reinforced embankments. The analysis was used in a case study on a controlled stage-constructed embankment on soft ground in order to investigate its probabilistic stability. Modeling was performed by commercial geotechnical software usage (GeoStudio and RocScience packs, SIGMA/W+SLOPE/W and SLIDE³, respectively) and the reliability structural analysis was acquired by coupling this software with a reliability program. Then, two numerical models were simulated: a 2D and a 3D one. For this application, the First Order Reliability Method (FORM) was assumed for the reliability analyses. The statistical information, as well as the correlation between variable pairs, was based on a literature review. In total, 29 parameters were assumed as random variables (splitting parameters from different zones and layers). At the same time, the influence of the uncertainty level on reliability analysis and the sensitivity of parameters (assumed as random variables) were investigated. As a result, the reliability indexes obtained showed that the structure analyzed should not be considered with a satisfactory safety level. Meanwhile, the uncertainty level assumed for random variables can lead the probabilistic analysis to very different conclusions about the structural safety, and the most sensitivity parameters observed were the bulk unit weight (clay – soft soil – and fill material) and the undrained shear strength, followed by a slight importance of the initial void ratio.